Advancing Lignin Extraction Recovery from Natural Lignocellulosic Biomass into Biochemicals - Mohammad Siddique; Suhail Ahmed Soomro; Shaheen Aziz; Saadat Ullah Khan Suri; Muhammad Asif (Pakistan Journal of Analytical & Environmental Chemistry)
Worldwide population increase and economic development are the two reasons that signify a vital need to produce biofuels to fulfill contemporary energy demands. In this context, Lignocellulosic biomass as a renewable energy source has the potential to produce biofuel. It comprises of lignin, cellulose, and hemicellulose components. It can be considered a primary source of energy if utilized efficiently. Present research studies pinpoint to exploit locally accessible biomass sources to extract lignin from plants using an acid or alkali pretreatment. Lignin is extracted from biomass sources including the bark of babul (BTB) and neem tree bark (NTB). In this article, the proximate and final analyses are performed on the lignin separation using a pretreatment procedure. The characterization methods such as Energy dispersive spectroscopy (EDS), Scanning electron microscopy (SEM), and Thermogravimetric analysis (TGA) are performed. It is observed that BTB has an improved lignin recovery in comparison with NTB. On the other side, NTB produces a low lignin production around 12% after 5 h as compared to a 13% yield from BTB with the same time duration. Consequently, lignin greater yield is obtained utilizing BTB which can be further exploited in biomaterial production applications. This research outcome are promising and achieved with precise evaluation.